Analisis Penentuan Kedalaman Penanaman Pipa Flowline Untuk Mencegah Terjadinya Upheaval Buckling: Analysis of Determining the Depth of Flowline Pipe Planting to Prevent Upheaval Buckling - Jamal Rauf Husain; Arif Nurwaskito; Muhammad Syahril (Journal of Engineering Science and Technology Applications, 2023)
A force inside a pipe drains fluid from wells producing oil and natural gas. When the power works exceed the pipe's maximum resistance limit, it will cause deformation in the line. This research aimed to evaluate the height of the trench to determine the threshold of tremendous friction force working on the pipe to withstand the axial force, which can cause upheaval buckling. The method used is the calculation of stress analysis. The line of 12 inches measured its style and voltage was planted in the trench with l.5 meters high and 3 meters wide and the soil density of 14.70kN/m3. The data used in the calculation were the design pressure, the outside diameter of the pipe, the minimum melting point of the line, the design factor, the factor of pipe connections, the derating factor, the modulus young, the thermal expansion coefficient, the pipe installation temperature, the maximum operating temperature, the Poisson ratio, the internal pipe pressure, the sectional area of the inner pipe, the pipe cross-sectional area, the depth of pipe planting, the trench width, the value of pipe nondimension, and the soil density of flowline area. The analysis result indicated that the friction force is 356,025.71N/m, and the axial force is 44,927.35N/m. These results showed that the friction force working on the pipe could withstand the axial force working. The cost of making the trench can still be decreased by reducing the height of the track to l m. The excellent friction force in the channel with a size of lm is 252,501.92N/m, where the value is still more significant than the axial force. In conclusion, the friction force working with the trench lm high can still hold the axial force working on the pipe.